Stress And Strength Analyses On The Single Pilot Moveable Seat For The Ultra-Light Helicopter - Rosli, Mohamad Afiq Syarafuddin (Universiti Sains Malaysia, 2019)
The purpose of this thesis is to analyze the stress and strength, to design and to fabricate a moveable single pilot seat for an ultra-light helicopter (ULH). This thesis provides a detailed method in analyzing the stress and strength the single pilot moveable seat of an ultra-light helicopter and also the detail design of the moveable seat. The single moveable seat is designed so that it is capable of being shifted longitudinally (forward and backward) and able to rotated circumferentially around the centre post within a range of angles. The single moveable seat must be able to support a load of the pilot and other additional weight from a basic cockpit system which is implemented on this ultra-light helicopter where the total estimated is about 100 kg. This project uses the concept of Weight Shift Control (WSC) that is commonly used for a hang glider where the weight of the pilot itself controls the attitude of ULH. The selection of material used to complete this project is needed to ensure the strength of the selected material able to withstand to load applied to this moveable seat. The simulation analysis is done by using one of the computer-aided design (CAD) which is SOLIDWORKS 2016 X64 Edition software. The investigation is performed to observe whether the structure of the moveable single pilot seat can support the applied load or fail to deliver as required based on the several types of simulation testing. Instead of performing the analysis using a SOLIDWORKS software, the analytical approach are also calculated in this thesis to compare and verify the moveable seat structure manually. The two-dimensional equation of motion formula was used to calculate the stress of the structure. Both methods need to be performed to compare the simulation result with the analytical method and also to calculate the percentage difference between this two approaches. By comparing both of these approaches, the percentage difference is 0.084%. To complete this project, most of the material and equipment needs in fabricating this moveable seat model are available in the Aerospace workshop.